Factors affecting the work integrity of Wantannas employees - Afanti S Uloli; Hamidah; Agus Wibowo (Trigin Publisher, 2023)
The integrity of these employees is important because Wantannas is an agency that contains employees from various institutions such as the TNI and Polri. Of course, with this difference, it is necessary to have a unified institution, namely Wantannas, regardless of the origin of the institution.This research aims to improve work integrity at Wantannas. To improve work integrity, this research examines the influence of organizational culture, work discipline, and work motivation on work integrity at Wantannas. In this study, a sample of 115 Wantannas employees was used based on the Slovin formula. The results of this study indicate that organizational culture, work discipline, and work motivation have a significant effect on integrity in Wantannas. However, the findings of this study indicate that organizational culture has no significant effect on work discipline. Meanwhile, work motivation can have a direct effect on work discipline at Wantannas. Suggestions for further research are presented in this study So that further researchers can add other variables as intervening such as employee satisfaction